Konsekuensi Environmental Concern dan Social Influence pada Skincare Ramah Lingkungan - Satiti Satiti; Fatik Rahayu; Robert Kristaung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the influence of environemental concern dan social influence on purchase intention and willingness to pay for the purchase of eco-friendly skincare products. Sampling in this study used purposive sampling technique by selecting samples, which are individuals who have purchased eco-friendly skincare products in the past year. The research was conducted by distributing questionnaires online to obtain primary data. The validity test and reliability test were conducted to test the instrument for each indicator. The data analysis method used to test the hypothesis in this study is the Structural Equation Model (SEM).